Ten lectures on event structure in a network theory of language - Gisborne, Nikolas, 1966- (Distinguished lectures in cognitive linguistics., 2020)
"In Ten Lectures on Event Structure in a Network Theory of Language, Nikolas Gisborne explores verb meaning. He discusses theories of events and how a network model of language-in-the-mind should be theorized; what the lexicon is; how to probe word meaning; evidence for structure in word meaning; polysemy; the lexical semantics of causation; a type hierarchy of events; and event types cross-linguistically. He also looks at the relationship between different classes of events or event types and aktionsarten; transitivity alternations and argument linking. Gisborne argues that the social and cognitive embedding of language, requires a view of linguistic structure as a network where even the analysis of verb meaning can require an understanding of the role of speaker and hearer"--